Controversial reasoning in Indian philosophy: major texts and arguments on Arthapātti - Keating, Malcolm (Bloomsbury Academic, 2020)
A pervasive form of reasoning exists in Indian philosophy. Known as Arthāpatti, this epistemic instrument is crucial to Mimamsa philosophers, as well as a point of controversy for Nyaya and Buddhist philosophers, yet to date it has received less attention than perception, inference, and testimony. This collection presents a one-of-a-kind reference resource for understanding this form of reasoning in Indian philosophy. It assembles translations of central primary texts by Kumarila Bhatta, Prabhakara Misra, Jayanta Bhatta, Udayana and Gangesa Upadhyaya, together with newly-commissioned essays on research topics. These readable translations of Sanskrit works are accompanied by critical notes which introduce arthapatti, offer historical context, and clarify the philosophical debates surrounding it. Showing how arthapatti is used as a way to reason about the basic unseen causes driving language use, cause-and-effect relationships, as well as to interpret ambiguous or figurative texts, this book demonstrates the importance of this epistemic instrument in both contemporary Anglo-analytic and classical Indian epistemology, language, and logic